SOME PROBLEMS OF CREATING ELECTRIC ENVIRONMENTALLY FRIENDLY AIRCRAFT - V. P. Kharkov (Naučnyj Vestnik MGTU GA, 2016)
In the article the questions connected with the possibility of creating environmentally friendly electric aircraft are considered. It is suggested to use modern accumulators based on the lithium-thionyl chloride as a source of electrical energy.